Fractional Dynamic Sliding Mode Control for Uncertain Chaotic Systems Applied to a Chaotic Robot Arm Under Dynamic Load - P., Sara G.; Minagar, Sara; Kazemitabar, Javad; Alizadeh, Mobin (International Journal of Sensors Wireless Communications and Control, 2020)
Background: A novel type of control strategy is presented for the control of chaotic systems, particularly a chaotic robot in joint and workspace, which is the result of applying fractional calculus to dynamic sliding mode control. Objectives: To guarantee the sliding mode condition, a control law is introduced based on the Lyapunov stability theory. Methods: A control scheme is proposed for reducing the chattering problem in finite time tracking and robust in the presence of system matched disturbances. Results: Qualitative and quantitative characteristics of the chaotic robot are all proven to be viable thru simulations. Conclusion: In addition, all of the chaotic robot’s qualitative and quantitative characteristics have been investigated. Numerical simulations indicate the viability of our control method.
Keywords: poincaré map